The Role of Self-Care Behavior to Thai Traditional Medicine for Elderly: Case of Ban Dung, Udon Thani Province - Mekwimon Kingkaew, Wanwimon; Siraphatthada, Yananda; Thitivesa, Duangkamol; Rattamanee, Komkrit (International Journal of Psychosocial Rehabilitation, 2020)
Self-care is a multi-dimensional process in which a number of engagement activities are included so that the healthy functioning as well as the well-being of a person can be ensured. The overall self-care behavior includes three major dimensions i.e. utilization of organization’s resources and support, organizational practices and self-care practices. The current study has the motive to find out and explore the impact of utilization of organizational resources and support, organizational practices and self-care practices on the life quality of elderly along with the mediating impact of mental life of the elderly in the organizations of Ban Dung, Udom Thai province. For research purpose, the researcher collected the data from elderly employees and 321 responses were considered for analysis. The results have suggested that the impact of organizational practices and self-care practices has significant impact on the life quality of elderly but the impact of utilization of organizations support and resources does not have the significant impact in this regard. In addition, the mediating impact of mental health of elderly is significant in case of utilization of organizational resources and support and self-care practices but is insignificant in case of organizational practices.